Global norms, organisational change: framing the rights-based approach at ActionAid - Magrath, Bronwen (Taylor & Francis, 2014)
This article examines the adoption of the rights-based approach (RBA) to development at ActionAid International, focusing in particular on its Education Theme. Although there has been a considerable volume of work that examines the rise of RBA, including in the pages of Third World Quarterly, the power dynamics and conflict involved in shifting to RBA have largely gone unnoticed and explored. Using the methodological tools of discourse analysis and social movement theory on strategic issue framing, I examine how ActionAid leadership worked to ‘sell’ RBA to somewhat-resistant staff and partners. I argue that ActionAid struggled to reconcile its commitment to global rights norms with the ongoing needs-based programming at country-level. This raises important questions about the power dynamics involved when an NGO undergoes a process of organisational change, even when, as is the case with RBA, this is widely seen as a progressive and desirable transition.